Analisis Buku Pendidikan Agama Islam Pelajaran Akidah Dan Akhlak I Madrasah Tsanawiyah Kelas VII - Nur Hidayat (At-Ta'lim : Media Informasi Pendidikan Islam, 2022)
Abstract: Analysis of Islamic Religious Education Books Subjects of Faith and Morals I 8th Grade Madrasah Tsanawiyah.This research is a content analysis that aims to describe: (1) the order of the material; (2) linguistic aspects; (3) the relevance of the proposition; (4) deficiencies or weaknesses in textbooks; and (5) recommendations. This research was conducted using a qualitative approach using content analysis techniques, with the main data source in the form of Islamic Religious Education Textbooks (Aqidah and Morals 1) for class VII Madrasah Tsanawiyah curriculum 2013, published by PT Tiga Serangkai Pustaka Mandiri. Based on the results of the analysis of the textbooks, it can be concluded that: in general, Islamic Religious Education Textbooks (Aqidah and Morals 1) for Madrasah Tsanawiyah Class VII Curriculum 2013 are appropriate books to be used as reading material and references in learning Islamic Religious Education, especially material on moral creed. The discussion material is in accordance with the curriculum, core competencies, and basic competencies.Abstrak: Analisis Buku Pendidikan Agama Islam Pelajaran Akidah Dan Akhlak I Madrasah Tsanawiyah Kelas VIIPenelitian ini adalah analisis konten yang bertujuan untuk mendeskripsikan: (1) urutan materi; (2) aspek kebahasaan; (3) relevansi dalil; (4) kekurangan/kelemahan pada buku ajar; dan (5) rekomendasi. Penelitian ini dilakukan dengan pendekatan kualitatif menggunakan teknik analisis isi dengan sumber data utama berupa Buku teks Pendidikan Agama Islam (Akidah dan Akhlak 1) untuk kelas VII Madrasah Tsanawiyah kurikulum 2013 terbitan PT Tiga Serangkai Pustaka Mandiri. Berdasarkan hasil analisis dari buku ajar, dapat disimpulkan bahwa: Secara umum, buku Teks Pelajaran Pendidikan Agama Islam (Akidah dan Akhlak 1) untuk Madrasah Tsanawiyah kelas VII Kurikulum 2013 merupakan buku yang layak untuk dijadikan bahan bacaan dan rujukan dalam pembelajaran Pendidikan Agama Islam khusunya materi akidah ahlak. Materi pembahasannya sudah sesuai dengan kurikulum, kompetensi inti dan kompetensi dasar.